Play Therapy with Digital Media Augmented Reality Cards to Improve Memory and Fine Motor Skills in Children - Dadi Hamdani; Andan Firmansyah; Iif Taufiq El Haque; Gumelar Zati Rahayu; Ade Koswara; Akmal Rahayu Dasuki Rahmat; Alfi Fadilah; Muhammad Daffa Alifio; Mohammad Haekal; Muhammad Syahrul Zain (Yayasan Inspirasi El Burhani, 2022)
Introduction: The development and support of digital technology have provided new opportunities to provide learning in the form of interesting educational games for early childhood. Because children are closely related to games, digital educational games are a strategic step to provide new experiences in learning, especially to improve children's memory and fine motor skills. Purpose: The purpose of this community service is to carry out play therapy using card media with Augmented Reality which children have never done before. Methods: Play therapy activities focused on school-age children are carried out by lecturers and a group of students from the D3 Nursing Study Program STIKes Muhammadiyah Ciamis. The method in play therapy activities uses simulation methods and direct practice in games using Augmented Reality card media. Location This service was held at SDN 1 Kalipucang Pangandaran with 20 students participating. Results: This community service activity can illustrate how play therapy improves fine motor skills and memory in early childhood by using the Augmented Reality card approach that is displayed on the cellphone screen and changes from a 2-dimensional image to a 3-dimensional image. The children became very enthusiastic and became very curious about what kind of images would appear from the Augmented Reality cards they held. The overall age of children is (6-13 years) and in this game, they have memory and fine motor skills that are quite good according to their developmental age. Conclusion: During the play therapy activities, it was successful and it was concluded that children were able to remember and know what type of cards and objects or creatures they were exploring with the help of a smartphone screen.